Preparation method of high-pressure-resistant high-power-salt concentrated composite nanofiltration membrane and nanofiltration membrane thereof
The integration of a core-shell terpolymer and naphthalene ring structure in the nanofiltration membrane preparation process addresses the stability and desalination challenges of high-salt wastewater treatment, resulting in a membrane with improved pressure resistance and efficient salt concentration performance.
Patent Information
- Application Number
- CN202411780257.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-01-03
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing high-salt wastewater treatment methods face challenges in achieving efficient, high-pressure operation stability and suitable desalination rates due to the poor performance of conventional nanofiltration membranes, particularly in high-salt environments, leading to increased energy consumption and operational costs.
A method involving the use of a core-shell structure terpolymer and naphthalene ring structure in the polyamide layer during interfacial polymerization to enhance the toughness and rigidity of the nanofiltration membrane, ensuring better pressure stability and desalination performance under high-pressure conditions.
The prepared nanofiltration membrane exhibits reduced flux attenuation and maintains stable desalination performance, enabling efficient concentration of high-salt wastewater with lower energy consumption, achieving a sodium chloride removal rate of 75-95% and concentrating influent TDS from 42,000-55,000 ppm to 85,000-160,000 ppm under 70-100 Bar pressure.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of nanofiltration membranes, and in particular relates to a preparation method of a high-pressure resistant high-salt concentration composite nanofiltration membrane and a nanofiltration membrane thereof. Background Art
[0002] Membrane separation technology, with its advantages of simple operation process, low energy consumption, high selectivity and continuous operation, meets the needs of modern industrial development for energy conservation, environmental protection, high efficiency, low cost and low pollution. It has been widely used in various fields such as water treatment, biotechnology, food and beverage, pharmaceuticals, and chemicals, and is an important technical support for achieving sustainable economic development. According to the characteristics of the membrane, membrane separation mainly includes four types: microfiltration membrane, ultrafiltration membrane, nanofiltration membrane and reverse osmosis membrane. Among them, nanofiltration membrane has attracted more and more attention due to its special molecular weight cutoff and excellent ion selectivity. Compared with conventional water treatment nanofiltration membrane, with the gradual extension of application ends in various subdivided fields, the demand for various special nanofiltration membranes has become more and more diversified. These include high temperature resistant, solvent resistant and high pressure resistant nanofiltration membranes. Among them, high pressure nanofiltration membranes are mainly used in seawater desalination, high concentration of pharmaceutical intermediates, zero emission and resource utilization of high-salt wastewater.
[0003] High-salt wastewater mainly refers to wastewater containing organic matter and at least a total dissolved solids mass fraction greater than 3.5%, containing high concentrations of chloride ions, sulfate ions, sodium ions, etc. Due to its high salt content, it has a strong inhibitory effect on the growth of microorganisms. The treatment of this wastewater is more difficult than ordinary sewage. Traditional high-salt wastewater treatment mainly uses methods such as chemical addition or evaporation concentration to achieve resource utilization of high-salt wastewater, which has the characteristics of low treatment efficiency and high operating costs. The current mainstream method for high-salt wastewater treatment mainly adopts multi-mechanism coupling process, among which the double membrane separation and concentration technology has unique application advantages in high-salt wastewater treatment and its resource utilization due to its high-efficiency selective separation, green environmental protection, and low operating energy consumption. The double membrane process first uses a conventional nanofiltration membrane segment to efficiently remove most of the sulfate, calcium, magnesium and other ions in the wastewater to obtain a crude sodium chloride salt solution with a salt concentration of 3wt%-5.5wt%, and then uses a relatively high desalination rate concentration nanofiltration membrane segment to concentrate the salt solution from the initial concentration of 3wt%-5.5wt% to 6wt%-16wt%. Compared with evaporation concentration, this process greatly reduces energy consumption. At the same time, the concentrated 6-16wt% sodium chloride solution can be directly used as a raw material for the chlor-alkali or soda ash industry. For the chlor-alkali or soda ash industry, due to the low cost of high-salt wastewater, the cost of raw materials in the process chain can also be greatly saved.
[0004] For the above-mentioned double-membrane technology for resource utilization of high-salt wastewater process, the performance of the back-end concentrated nanofiltration membrane is crucial to the degree of salt solution concentration. First of all, due to the high concentration in high-salt wastewater, membrane separation technology requires a higher driving pressure to achieve the separation effect, so the used concentrated nanofiltration membrane must meet the requirements of better high-pressure operation stability. At the same time, since the salt concentration of the influent is already quite high, the higher concentration of the sodium chloride solution in the raw water on this basis requires the concentrated nanofiltration membrane to have a relatively suitable desalination rate and a higher initial water production. If the membrane desalination rate is too high, according to the principle of osmotic pressure, the pressure on the inlet side needs to be doubled to maintain a relatively stable water production, and the demand for equipment and operating energy consumption will be greatly increased accordingly; if the desalination rate is low, it is impossible to greatly increase the TDS content on the concentrated water side to meet the basic needs of further concentrating the salt solution. In summary, the back-end concentrated nanofiltration membrane of this process must have excellent pressure stability and suitable sodium chloride removal performance. In the Chinese invention patent document with publication number CN108246128A, the inventor used aliphatic amines and aliphatic acyl chlorides to prepare a loose nanofiltration membrane with a sodium chloride removal rate of 57-75% through interfacial polymerization, but its stability is poor and its industrial application needs further verification. In the Chinese invention patent document with publication number CN113908705A, the inventor used amine aqueous phase solution, oil phase solution and dimethylformamide solution to treat the base membrane, and prepared a loose nanofiltration membrane with a removal rate of 70-90% through a special component ratio in the amine aqueous phase solution and the oil phase solution, but it mainly considers the application in low-pressure and low-salt environments, and does not mention the changes in desalination and flux and their stability in high-pressure operation scenarios. In another Chinese invention patent document with publication number CN114797495A, the inventor considered adding carbon nanotubes to a polysulfone-based membrane to prepare a high-pressure resistant nanofiltration membrane that can remove more than 90% of sodium chloride. However, the carbon nanotubes used are relatively expensive, and their stability in long-term operation is still unclear. Summary of the invention
[0005] The object of the present invention is to provide a method for preparing a nanofiltration membrane and the nanofiltration membrane thereof. The preparation method is simple and easy to operate, and the prepared nanofiltration membrane can be used for high-pressure and high-multiple salt concentration.
[0006] To solve the above problems, the technical solution adopted by the present invention is: In a first aspect, the present invention provides a method for preparing a nanofiltration membrane, comprising the following steps: (1) taking a certain amount of polysulfone particles, a core-shell structure terpolymer, a hydrophilic additive and N,N-dimethylformamide, mixing and stirring to prepare a casting solution; (2) scraping the casting liquid onto a non-woven fabric substrate by a casting method to form a base film, and storing it in pure water; (3) contacting the base film with an aqueous solution containing a polyamine monomer, and removing excess solution to obtain a treated base film; (4) contacting the treated base film with an organic solution containing a polyacyl chloride monomer and an acyl chloride monomer having a naphthalene ring structure to cause an interfacial polymerization reaction; (5) subjecting the reaction product of step (4) to air heating treatment to promote further cross-linking of the polyamide layer and volatilize the organic phase solution to obtain an initial nanofiltration membrane; (6) immersing the initial nanofiltration membrane in a citric acid solution for post-treatment to wash away unreacted monomers and additives; (7) washing the initial nanofiltration membrane after cleaning in step (6) with pure water at room temperature to cool the membrane, clean the citric acid and other substances contained in the membrane, and then immersing it in a glycerol solution for pore preservation pretreatment; (8) The nanofiltration membrane after the pore preservation pretreatment is taken out and heated and dried to obtain the final concentrated nanofiltration membrane.
[0007] Among them, steps (1) to (2) are the preparation process of the base membrane, and steps (3) to (8) are the preparation process of the high-pressure concentrated nanofiltration membrane. The difference of the present invention is that a core-shell structure terpolymer is introduced into the base membrane to enhance the pressure impact resistance of the base membrane. At the same time, during the interfacial polymerization process, naphthalene rings are introduced to improve the rigidity of the polyamide layer, thereby reducing the change rate of the flux and desalination of the nanofiltration membrane due to compaction under high pressure conditions.
[0008] The various steps of the preparation method of the present invention are described in detail below. If not otherwise specified, the various raw materials used in the preparation method of the present invention can be commercially obtained or prepared by known methods. In addition, if the type of solvent is not otherwise specified, the solution used in the preparation method of the present invention is an aqueous solution.
[0009] In step (1), a certain amount of polysulfone particles, a core-shell structure terpolymer, a hydrophilic additive and N,N-dimethylformamide are mixed to prepare a casting solution; different from the prior art, the present invention introduces a core-shell structure terpolymer into the polysulfone layer to improve the toughness of the support layer base membrane material and improve the compressive performance of the substrate. Under high-pressure testing, it can absorb part of the stress and reduce the compaction degree of the polysulfone layer, ensuring that the polysulfone layer can still have a water-conducting channel that meets the requirements; In the casting solution, the mass fraction of polysulfone is 15-25 wt%, and 21 wt% is preferred in the present invention; if the polysulfone content is too low, the mechanical strength of the support layer cannot meet the high-pressure use requirements; if the polysulfone content is too high, the porosity of the substrate is low, and the water permeability is too low to meet the needs of subsequent concentration experiments; the content of the core-shell structure terpolymer is about 10-30% of the mass of polysulfone, preferably 20%, if the addition amount of the core-shell copolymer is too low, the effect of improving the bearing strength of the support layer is not obvious, and if the addition amount is too high, the viscosity of the casting solution will be too high, and due to the solubility limitation of the core-shell copolymer, too high an addition amount is not conducive to the preparation of a homogeneous casting solution, and the core-shell polymer includes one or more of methyl methacrylate-butadiene-styrene copolymer, ethylene-butyl acrylate-glycidyl methacrylate copolymer, ethylene-methyl acrylate-glycidyl methacrylate copolymer, and ethylene-methyl methacrylate-glycidyl methacrylate copolymer; The hydrophilic additive is polyethylene glycol, the molecular weight of the polyethylene glycol is 200-100000 Da, and the content of the polyethylene glycol is 3-5 wt% of the mass of the casting solution, preferably 4 wt%. If the hydrophilic additive is too low, the pore-forming effect of the support layer base membrane is not obvious, and if the addition amount is too high, it will affect the solid-liquid phase separation and phase conversion process, which is not conducive to the preparation of a support layer with high pressure bearing strength.
[0010] The casting solution is stirred at a temperature of 75-85°C for 6 hours, vacuum degassing is performed and the casting solution is allowed to stand at 20-30°C. In step (2), the casting solution prepared in step (1) is scraped onto a non-woven fabric substrate by a casting method to form a base film, and the base film is stored in pure water; the base film mainly consists of two parts, including a polysulfone layer and a non-woven fabric layer, the non-woven fabric layer is selected from one of polyester or polypropylene, and the base film has a thickness of 150-165 one ; In step (3), the base film obtained in step (2) is contacted with an aqueous solution containing polyamine monomers, and excess solution is removed; the aqueous solution of polyamine monomers comprises: polyamine monomers, co-solvents, acylation catalysts, acid binding agents and water; The polyamine monomer is selected from one or more of m-phenylenediamine, p-phenylenediamine, o-phenylenediamine, mesitylenetriamine, ethylenediamine, 1,3,4-triaminobenzene, 3,5-diaminobenzoic acid, 2,4-diaminotoluene, diethylenetriamine, triethylenetetramine, piperazine, 1-ethylpiperazine, and polyethyleneimine. The polyamine monomer content in the aqueous solution containing the polyamine monomer is 0.1-10 wt %, preferably 1-5 wt %; The co-solvent is mainly selected from one or more of N-methylpyrrolidone, N-ethylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, ethanol, ethylene glycol, isopropanol, and dimethyl sulfoxide. The content of the co-solvent is 0.1-20wt%, preferably 5-14wt%. The co-solvent acts as a co-solvent during the interfacial polymerization reaction to promote the diffusion and dissolution of the aqueous phase monomer, thereby improving the performance of the prepared nanofiltration membrane. The acylation catalyst comprises 4-dimethylaminopyridine, and the content of the acylation catalyst in the aqueous solution containing the polyamine monomer is 0.01-1wt%; the acylation catalyst mainly functions to promote the reaction between the amino group and the acyl chloride group on the structure containing the large sterically hindered naphthalene ring, promote the rigid naphthalene ring to enter the polyamide chain, and improve the compressive resistance of the separation layer of the nanofiltration membrane; The acid binding agent is selected from one or more of a triethylamine / camphorsulfonic acid composite system, sodium hydroxide, potassium hydroxide, dipotassium hydrogen phosphate, and sodium carbonate. The amount of the acid binding agent is regulated by the pH value of the aqueous solution of the polyamine monomer, and the pH value of the aqueous solution is 10-11; The contact time between the base film and the aqueous solution containing the polyamine monomer is preferably 10 to 60 seconds. The contact temperature is not limited and can be room temperature or within the temperature range of 15 to 45°C; In step (4), the base film obtained in step (3) is contacted with an organic solution containing both a polyacyl chloride monomer and an acyl chloride monomer having a naphthalene ring structure to cause an interfacial polymerization reaction; The polyacyl chloride monomer is an acyl chloride monomer having two or more acyl chloride groups; preferably, the polyacyl chloride monomer includes one or more of trimesoyl chloride, cyanuric chloride, isophthaloyl chloride, terephthaloyl chloride, phthaloyl chloride, biphenyl tetrachloride, biphenyl dichloride, benzene disulfonyl chloride, butane trichloride, glutaryl trichloride, cyclobutane dichloride, and cyclohexane dichloride; the content of the polyacyl chloride monomer is 0.05-1 wt% of the total mass of the organic phase, preferably 0.1-0.5 wt%. When the concentration is lower than 0.05 wt%, a good polyamide layer cannot be formed to meet the performance requirements of the nanofiltration membrane; when the concentration is higher than 1 wt%, the flux of the prepared nanofiltration membrane is low and cannot meet the application requirements; The acyl chloride monomer with a naphthalene ring structure is used as the second monomer, and its main characteristics are: there is a main naphthalene ring, and there are 1 to 3 acyl chloride or sulfonyl chloride groups in its structure. According to the structure, one or more of 1,3,6-naphthalene trisulfonyl chloride, 2,6-naphthalene disulfonyl chloride, 2,7-naphthalene disulfonyl chloride, naphthalene-1,5-disulfonyl chloride, 2,6-naphthalene dicarbonyl chloride, 5-(dimethoxy)naphthalene-1-sulfonyl chloride, 1-naphthalene carbonyl chloride, 2-naphthalene carbonyl chloride, and 2-naphthalenesulfonyl chloride can be selected; the purpose of introducing the naphthalene ring is to improve the rigidity of the polyamide chain and ensure the stability of the flux and desalination performance of the nanofiltration membrane under high pressure operation. The content of the acyl chloride monomer with a naphthalene ring structure is 0.01 to 1 wt%, preferably 0.02 to 0.5 wt%. When the content of the naphthalene ring acyl chloride is too low, due to the limitation of the reaction activity, the pressure bearing effect of the separation layer is not significantly improved, and the relatively high addition of the naphthalene ring acyl chloride will greatly reduce the desalination rate of the membrane, which is difficult to meet the needs of subsequent concentration experiments. In the organic solution containing polyacyl chloride monomers and acyl chloride monomers having a naphthalene ring structure, the organic solvent is selected from one or more of low polar solvents such as n-hexane, n-heptane, cyclohexane, n-octane, Isopar M, Isopar H, Isopar L, Isopar E or Isopar G.
[0011] The base film is in contact with the organic solution containing the polyacyl chloride monomer and the acyl chloride monomer having a naphthalene ring structure for 10 to 60 seconds. The contact temperature is not limited and can be room temperature or within a temperature range of 15 to 45°C.
[0012] In step (5), the reaction product of the interfacial polymerization reaction in step (4) is subjected to air heating treatment to promote further cross-linking of the polyamide layer and volatilize the organic phase solution to prepare an initial nanofiltration membrane; The air heating temperature is 60-80°C, and the heating time is 1-5 minutes. If the heating time is too long or the temperature is too high, the polyamide molecular chain on the membrane surface will break, affecting the desalination performance of the nanofiltration membrane. If the heating time is too short or the temperature is too low, the membrane surface will not dry and a more effective polyamide layer cannot be formed. In step (6), the initial nanofiltration membrane obtained in step (5) is immersed in a citric acid solution for post-treatment to wash away unreacted monomer additives; The concentration of the citric acid solution is 0.5-10 wt%, the cleaning temperature is 60-80°C, and the cleaning time is 5-10 minutes; In step (7), the nanofiltration membrane obtained in step (6) is washed with pure water at room temperature to cool the membrane and clean the citric acid and other substances contained in the membrane, and then immersed in a glycerol solution for pore preservation pretreatment; The room temperature water is mainly 20-30°C pure water, and the cleaning time is 3-15 minutes, preferably 5-10 minutes; if the cleaning time is too short, the residual substances on the membrane surface and membrane pores cannot be cleaned, and if the cleaning time is too long, it is not conducive to improving the efficiency of the preparation process; The concentration of the glycerol solution is 10-15 wt %, the temperature of the glycerol solution is 20-30° C., and the immersion time of the glycerol solution is 0.5-5 minutes, preferably 2-3 minutes; if the immersion time is too short, the glycerol solution cannot be completely infiltrated, and if the immersion time is too long, there is a risk of swelling of the primary separation layer of the composite membrane; In step (8), the nanofiltration membrane obtained in step (7) is subjected to a heating and drying treatment to obtain a final nanofiltration membrane; The heating and drying method adopts air heating and drying, and the temperature is 60-90°C, preferably 70-80°C. If the heating temperature is too high, the membrane surface will be too dry, so that the membrane flux is reduced. If the heating temperature is too low, the membrane surface will not be dry, and a stable polyamide layer cannot be formed. The heating time is 1 to 15 minutes and can be adjusted according to actual conditions to ensure that the film surface is just dry.
[0013] In a second aspect, the present invention also provides a concentrated nanofiltration membrane prepared according to the preparation method. The nanofiltration membrane can be prepared according to the optimization of additives, for example, having a water flux of 40-65 GFD and a sodium chloride removal rate of 75-95%. (Conditions: 32000 mg / L sodium chloride solution, pressure 800 psi, temperature 25°C). The concentrated nanofiltration membrane can be applied to the fields of high-salinity wastewater treatment and resource recycling.
[0014] Beneficial effects: The technical solution provided by the present invention improves the pressure-bearing effect of the composite nanofiltration membrane through a composite solution. First, by introducing a core-shell structure ternary copolymer as an additive in a polysulfone base membrane, the introduction of the additive can greatly improve the toughness of the base membrane of the support layer. Based on the improvement of the toughness of the support layer, the compressive impact strength of the support layer can be greatly improved, thereby improving the compression resistance of the support layer under continuous high-pressure operation conditions, ensuring the retention of the water-conducting channel in the base membrane material of the support layer under high pressure; on the other hand, a naphthalene ring structure organic phase monomer is introduced in the interfacial polymerization reaction, so that the polyamide segment in the prepared separation layer contains a certain proportion of naphthalene ring structure. Since the naphthalene ring itself has a strong structural rigidity, the prepared separation layer has a stronger rigidity than the conventional polyamide membrane material, which is more conducive to the maintenance of the separation performance during continuous operation under high pressure conditions. In summary, the preparation of the high-pressure high-salt concentration composite nanofiltration membrane described herein not only improves the impact toughness of the substrate, but also realizes the construction of the rigid structure of the separation layer, and solves the problem of poor pressure stability of conventional polyamide composite nanofiltration membrane materials from the material body. Secondly, the higher water permeability and relatively moderate desalination rate of the prepared nanofiltration membrane are also more conducive to the membrane system to achieve more efficient concentration at lower operating energy consumption.
[0015] The concentrated nanofiltration membrane prepared by this method has a lower flux attenuation than the original membrane in a high-pressure environment for a certain period of time, and a relatively stable desalination performance; The concentrated nanofiltration membrane prepared by this method can concentrate the influent TDS from 42000-55000ppm to 85000-160000ppm under the high pressure operation condition of 70-100Bar; The nanofiltration membrane prepared by this method can adjust the interfacial polymerization conditions to prepare a high-pressure concentrated nanofiltration membrane with a sodium chloride removal rate of 75~95%. DETAILED DESCRIPTION
[0016] The technical scheme of the present invention is further described in detail below in conjunction with the examples, but is not intended to limit the present invention. It should be noted that the reagents and raw materials used in the examples of the present invention are all commercially available conventional products unless otherwise specified. Example
[0017] Preparation of base film: Prepare casting solution with 21 wt% polysulfone particles, 4 wt% polyethylene glycol 2000, and the balance N,N-dimethylformamide, stir at 80°C for 6 hours, use vacuum degassing, and place at room temperature for use. Use casting method to scrape the casting solution onto polyester non-woven fabric, the base film thickness is 152um, use water as a coagulant to solidify the casting solution into a film, and then wash it with water for use, to prepare base film 1; The same process as above was followed, and the casting solution was divided into three parts, and 4.2 wt% of methyl methacrylate-butadiene-styrene copolymer, ethylene-butyl acrylate-glycidyl methacrylate copolymer, and ethylene-methyl acrylate-glycidyl methacrylate copolymer were added respectively to prepare base film 2, base film 3, and base film 4, respectively.
[0018] Preparation of polyamine solution: 2.5 wt% m-phenylenediamine, 0.5 wt% triethylamine, 4 wt% camphorsulfonic acid, 5 wt% ethylene glycol, 0.03 wt% 4-dimethylaminopyridine, and the balance of pure water were stirred to prepare a polyamine solution; Preparation of acyl chloride solution: 0.2 wt% trimesoyl chloride and the balance of Isopar L were used to prepare polyacyl chloride solution 1; while maintaining the total acyl chloride monomer concentration unchanged, part of the trimesoyl chloride monomer was replaced with an acyl chloride monomer containing a naphthalene ring structure, wherein 0.05 wt%, 0.10 wt%, 0.15 wt% and 0.20 wt% 1,3,6-naphthalenetrisulfonyl chloride were used to prepare polyacyl chloride solutions 2 to 5, and 0.05 wt% 2,6-naphthalene disulfonyl chloride, 0.05 wt% 2,6-naphthalene dicarbonyl chloride, 0.05 wt% 2-naphthalenecarbonyl chloride, 0.05 wt% 5-(Dimethoxy)naphthalene-1-sulfonyl chloride was used to prepare polyacid chloride solution 6~9. Comparative Example
[0019] The base membrane 1 stored in pure water is taken out and fixed, and immersed in a room temperature polyamine solution for 30 seconds to adsorb amine monomers. After removing excess surface solution, it is placed in a room temperature polyacyl chloride solution 1 for 30 seconds for interfacial polymerization reaction. The nascent nanofiltration membrane is placed in a 60-70°C environment for heat treatment to promote further cross-linking of the polyamide layer. After the treatment time is about 5 minutes, the prepared nanofiltration membrane is immersed in a 65-70°C 1.5 wt% citric acid solution for cleaning, and then placed in pure water at about 25°C for cleaning for 8 minutes. The cleaned nanofiltration membrane is placed in a room temperature 12wt% glycerol solution for 2 minutes to allow the base membrane to adsorb the glycerol aqueous solution. The membrane is placed in a 70-80°C oven and dried for 6-8 minutes to obtain the final nanofiltration membrane. Comparative Example 1
[0020] The base membrane 2 stored in pure water is taken out and fixed, and immersed in a room temperature polyamine solution for 30 seconds to adsorb amine monomers. After removing excess surface solution, it is placed in a room temperature polyacyl chloride solution 1 for 30 seconds for interfacial polymerization reaction. The nascent nanofiltration membrane is placed in a 60-70°C environment for heat treatment to promote further cross-linking of the polyamide layer. After the treatment time is about 5 minutes, the prepared nanofiltration membrane is immersed in a 65-70°C 1.5 wt% citric acid solution for cleaning, and then placed in pure water at about 25°C for cleaning for 8 minutes. The cleaned nanofiltration membrane is placed in a room temperature 12wt% glycerol solution for 2 minutes to allow the base membrane to adsorb the glycerol aqueous solution. The membrane is placed in a 70-80°C oven and dried for 6-8 minutes to obtain the final nanofiltration membrane.
[0021] The difference from the comparative example is that in the comparative example 1, the base film 2 is a base film containing methyl methacrylate-butadiene-styrene copolymer. Comparative Example 2
[0022] The base membrane 1 stored in pure water is taken out and fixed, and immersed in a room temperature polyamine solution for 30 seconds to adsorb amine monomers. After removing excess surface solution, it is placed in a room temperature polyacyl chloride solution 2 for 30 seconds for interfacial polymerization reaction. The nascent nanofiltration membrane is placed in a 60-70°C environment for heat treatment to promote further cross-linking of the polyamide layer. After the treatment time is about 5 minutes, the prepared nanofiltration membrane is immersed in a 65-70°C 1.5wt% citric acid solution for cleaning, and then placed in pure water at about 25°C for cleaning for 8 minutes. The cleaned nanofiltration membrane is placed in a room temperature 12wt% glycerol solution for 2 minutes to allow the base membrane to adsorb the glycerol aqueous solution, and the membrane is placed in a 70-80°C oven and dried for 6-8 minutes to obtain the final nanofiltration membrane.
[0023] The difference from the comparative example is that the composition of the polyacyl chloride solution 2 dip-coated in the comparative example 2 is 0.15 wt % of trimesoyl chloride and 0.05 wt % of 1,3,6-naphthalenetrisulfonyl chloride. Example 1
[0024] The base membrane 2 stored in pure water is taken out and fixed, and immersed in a room temperature polyamine solution for 30 seconds to adsorb amine monomers. After removing excess surface solution, it is placed in a room temperature polyacyl chloride solution 2 for 30 seconds for interfacial polymerization reaction. The nascent nanofiltration membrane is placed in a 60-70°C environment for heat treatment to promote further cross-linking of the polyamide layer. After the treatment time is about 5 minutes, the prepared nanofiltration membrane is immersed in a 65-70°C 1.5 wt% citric acid solution for cleaning, and then placed in pure water at about 25°C for cleaning for 8 minutes. The cleaned nanofiltration membrane is placed in a room temperature 12 wt% glycerol solution for 2 minutes to allow the base membrane to adsorb the glycerol aqueous solution. The membrane is placed in a 70-80°C oven and dried for 6-8 minutes to obtain the final nanofiltration membrane. Example 2
[0025] The preparation process is the same as that of Example 1, except that base film 2 is replaced by base film 3; Example 3
[0026] The preparation process is the same as in Example 1, except that the base film 2 is replaced with the base film 4; The main difference between Examples 1 to 3 is that the core-shell terpolymer contained in the base film is different; Example 4
[0027] The preparation process is the same as in Example 1, except that the polyacyl chloride solution 2 is replaced with the polyacyl chloride solution 3; Example 5
[0028] The preparation process is the same as in Example 1, except that the polyacyl chloride solution 2 is replaced with the polyacyl chloride solution 4; Example 6
[0029] The preparation process is the same as in Example 1, except that the polyacyl chloride solution 2 is replaced with the polyacyl chloride solution 5; Examples 1 and Examples 3-5 mainly investigate the influence of the proportion of 1,3,6-naphthalenetrisulfonyl chloride in the acyl chloride monomer solution. Example 7
[0030] The preparation process is the same as in Example 1, except that the polyacyl chloride solution 2 is replaced with the polyacyl chloride solution 6; Example 8
[0031] The preparation process is the same as in Example 1, except that the polyacyl chloride solution 2 is replaced with the polyacyl chloride solution 7; Example 9
[0032] The preparation process is the same as in Example 1, except that the polyacyl chloride solution 2 is replaced with the polyacyl chloride solution 8; Example 10
[0033] The preparation process is the same as in Example 1, except that the polyacyl chloride solution 2 is replaced with the polyacyl chloride solution 9; Examples 1 and Examples 7-10 mainly investigate the performance of membranes prepared from different acyl chloride monomers having a naphthalene ring structure.
[0034] Experimental Example 1 (1) Initial permeation separation performance test In order to test the performance of the prepared nanofiltration membrane, the nanofiltration membranes obtained in the comparative example, comparative examples 1 and 2, and examples 1 to 10 were tested on a cross-flow membrane test bench under the conditions of 32000 mg / L sodium chloride solution, operating pressure 800 psi, temperature 25°C, and pH value 7 to 8. The initial test stabilization time was 60 minutes, and the pressure resistance test time was 24 hours.
[0035]
[0036] From the comparative examples, the introduction of a core-shell structure ternary copolymer in the base membrane alone and the introduction of a naphthalene ring structure in the polyamide layer alone can significantly reduce the flux attenuation of the membrane after operation in a high-pressure environment, and the addition of 1,3,6-naphthalene trisulfonyl chloride as the second organic phase monomer can prepare a medium-desalination nanofiltration membrane with 75-95% sodium chloride removal. The introduction of a core-shell structure ternary copolymer can improve the compressive resistance of the base membrane of the support layer, reduce the compactness of the base membrane when subjected to high-pressure shock, and ensure the existence of some water-conducting channels; but in order to further prepare a high-pressure concentrated nanofiltration membrane with relatively high sodium chloride removal, consider introducing a naphthalene ring structure in the polyamide layer. From the comparative examples, the introduction of 1,3,6-naphthalene trisulfonyl chloride can prepare a nanofiltration membrane with a medium degree of removal, and the introduced naphthalene ring can improve the rigidity of the polyamide layer and reduce the flux attenuation during operation; From Examples 1 to 10, it can be seen that coupling the two methods can prepare a medium-desalination nanofiltration membrane with 75% to 95% sodium chloride removal, and can significantly improve the pressure-bearing performance of the nanofiltration membrane during high-pressure operation. From Examples 1 to 3, different core-shell structure ternary copolymers can bring good pressure resistance effect, but due to the difference in their own properties, the prepared nanofiltration membranes have certain differences in permeability and desalination performance; from Examples 1 and Examples 4 to 6, with the increase in the proportion of 1,3,6-naphthalenetrisulfonyl chloride in the organic phase monomer content, the membrane desalination can be reduced to 76.5%, and the flux is improved to a certain extent, and the prepared nanofiltration membrane still has relatively good pressure resistance; in addition, from Examples 1 and Examples 7 to 10, naphthalene ring structure-containing acyl chlorides containing trichlorides, dichlorides and monochlorides are used as common monomers to prepare nanofiltration membranes. From the results, the prepared nanofiltration membranes show relatively good pressure resistance after running for 24 hours in a high-pressure environment, and it is easier to prepare a nanofiltration membrane with a high desalination degree when the number of acyl chlorides is large. Therefore, by adjusting the monomers, a nanofiltration membrane with a sodium chloride removal rate of 75~95% can be prepared in a directionally manner.
[0037] Membrane elements and their sodium chloride concentration performance The wound membrane elements of the comparative example, comparative example 1, example 1, example 3 and example 7 were tested under the following test conditions: 32000 mg / L sodium chloride solution, operating pressure 800 psi, temperature 25°C, pH value 7-8, recovery rate 15%, and initial test stabilization time 60 minutes.
[0038]
[0039]
[0040] Note: The concentration experiment was carried out in a 6-core membrane element pressure vessel From the test results of membrane elements in Table 2, the desalination of the nanofiltration membrane prepared by the method of the present invention is in the range of 80-97%, and has a high permeability, which can be used for the concentration of high-concentration sodium chloride solution. From the concentration effect of Table 3, under the same concentration conditions, the nanofiltration membrane prepared by the embodiment has a better concentration effect. It can concentrate the sodium chloride aqueous solution with an influent TDS of 43050ppm to about 96300ppm, and with the increase of recovery rate and influent pressure, the TDS of the concentrated brine continues to increase, and can reach up to 136900ppm; further increase the raw water concentration to 54760ppm, and the raw water can be further concentrated to 160000ppm, showing a good concentration effect. That is, the concentrated nanofiltration membrane prepared by the method can concentrate the influent TDS from 42000-55000ppm to 85000-16000ppm under the high-pressure operation conditions of 70-100Bar; the nanofiltration membrane prepared by the invention method can adjust the interfacial polymerization conditions to prepare a high-pressure concentrated nanofiltration membrane with a sodium chloride removal rate of 75-95%.
[0041] In the specific implementation of the present invention, base film 1 is used for comparison with the technical solution of the present invention; different from base film 1, base film 2, base film 3 and base film 4 are respectively added with core-shell structure ternary copolymers: methyl methacrylate-butadiene-styrene copolymer, ethylene-butyl acrylate-glycidyl methacrylate copolymer, ethylene-methyl acrylate-glycidyl methacrylate copolymer. The inventor found that in other embodiments of the present invention, since shell-core ternary copolymers of different structures have good toughening effects, the addition of core-shell structure ternary copolymers can also adopt ethylene-methyl methacrylate-glycidyl methacrylate copolymer, or any combination of the above core-shell structure ternary copolymers, which can achieve the same or similar technical effects as base film 2, base film 3 or base film 4.
[0042] The inventors found that in the preparation of the above-mentioned base membrane, since the compressive stability of the support layer base membrane is mainly affected by the toughening effect of the core-shell structure terpolymer, in another embodiment of the present invention, under the premise of introducing the core-shell copolymer into the base membrane, the addition amount of polysulfone is in the range of 15~25 wt%, the molecular weight of polyethylene glycol is selected in the range of 200~100000 Da, the addition amount is in the range of 3~5 wt%, the non-woven fabric layer is selected from one of polyester or polypropylene, and the thickness of the base membrane is 150-165um, all of which can achieve the purpose of the present invention to improve the high-pressure stability of the composite nanofiltration membrane.
[0043] In Examples 1-10 of the present invention, the polyamine monomer used is m-phenylenediamine. The inventors have found that in other embodiments of the present invention, based on the introduction of the core-shell structure terpolymer into the base membrane and the introduction of naphthyl chloride by interfacial polymerization, the polyamine monomer can also be one or more of p-phenylenediamine, o-phenylenediamine, iso-phenylenediamine, ethylenediamine, 1,3,4-triaminobenzene, 3,5-diaminobenzoic acid, 2,4-diaminotoluene, diethylenetriamine, triethylenetetramine, piperazine, 1-ethylpiperazine, and polyethyleneimine. The polyamine monomer content of 0.1~10 wt% can achieve the effect of improving the high-pressure stability of the composite membrane. In order to further achieve the purpose of the high-multiple salt concentration experiment, the polyamine monomer content is controlled at 1~5 wt%, and the concentration effect is optimal.
[0044] In Examples 1-10 of the present invention, ethylene glycol is listed as the co-solvent used. The inventors found that in other embodiments of the present invention, based on the introduction of a core-shell structure terpolymer into the base membrane and the introduction of naphthyl chloride by interfacial polymerization, the co-solvent is selected from one or more of N-methylpyrrolidone, N-ethylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, ethanol, ethylene glycol, isopropanol, and dimethyl sulfoxide. The co-solvent content of 0.1-20wt% can achieve the effect of improving the pressure stability of the membrane. Considering the membrane flux and the appropriate desalination rate range required for the subsequent concentration experiment, 4-15wt% ethylene glycol is preferably used as a co-solvent for the polymerization reaction.
[0045] In Examples 1-10 of the present invention, the acid binding agents used are all triethylamine / camphorsulfonic acid compound agents. The inventors found that in other embodiments of the present invention, under the premise of introducing a core-shell structure terpolymer into the base membrane and introducing naphthyl chloride by interfacial polymerization, the acid binding agent is selected from one or more of sodium hydroxide, potassium hydroxide, dipotassium hydrogen phosphate, and sodium carbonate, and the pH value of the aqueous phase is controlled within the range of 10-11, which can achieve the effect of improving the pressure-bearing stability of the composite membrane.
[0046] In Examples 1-10 of the present invention, the organic phase monomers used include trimesoyl chloride. The inventors found that in other embodiments of the present invention, on the basis of introducing a core-shell structure terpolymer into the base membrane and introducing naphthyl chloride by interfacial polymerization, the organic phase monomers are selected from one or more of cyanuric chloride, isophthaloyl chloride, terephthaloyl chloride, phthaloyl chloride, biphenyltetrachloride, biphenyl dichloride, benzene disulfonyl chloride, butanetrichloride, glutaryl chloride, cyclobutanedichloride, and cyclohexanedichloride, and the content of the polyacyl chloride is 0.05-1wt%, which can achieve the effect of improving the pressure stability of the diaphragm. Preferably, an addition amount of 0.1-0.5wt% can achieve a better concentration effect.
[0047] In Examples 1-10 of the present invention, the second monomer naphthyl chloride used is one of naphthalene disulfonyl chloride, 2,6-naphthalene dicarbonyl chloride, 2-naphthalenecarbonyl chloride, and 5-(dimethoxy)naphthalene-1-sulfonyl chloride. The inventors found that in other embodiments of the present invention, under the premise of introducing a core-shell structure terpolymer into the base membrane, a combination of two or more of the above-mentioned naphthalene ring structure chlorides is selected, and an addition amount of 0.01-1wt% can also achieve the effect of improving the pressure-bearing stability of the composite membrane. Preferably, an addition amount of 0.02-0.5wt% can achieve a better concentration effect.
[0048] In Examples 1-10 of the present invention, the organic phase solutions listed are all Isopar-L. The inventors found that in other embodiments of the present invention, on the premise that the core-shell structure terpolymer is introduced into the base membrane and naphthyl chloride is introduced into the interfacial polymerization, the organic solvent is selected from other non-polar solvents such as: n-hexane, n-heptane, cyclohexane, n-octane, Isopar M, Isopar H, Isopar E or Isopar G. One or more combinations thereof can achieve the improvement of the pressure stability of the composite diaphragm.
[0049] In summary, the above embodiments fully illustrate that the method of improving the toughness of the base membrane material combined with the rigid structure of the separation layer adopted in the present invention has good formula and process adaptability in improving the overall high-pressure stability of the composite membrane, and the improvement of the high-pressure stability of the membrane is basically not affected by the monomer combination, the types of co-solvents and base membrane additives, and the types of organic phase solvents.
Claims
1. A method for preparing a high-pressure and high-salt concentration composite nanofiltration membrane, characterized in that: The steps include: (1) taking a certain amount of polysulfone particles, a core-shell structure terpolymer, a hydrophilic additive and N,N-dimethylformamide, mixing and stirring to prepare a casting solution; (2) scraping the casting solution onto a non-woven fabric substrate to form a base film by a casting method, and storing the base film in pure water; (3) contacting the base film with an aqueous solution containing a polyamine monomer, and removing excess solution to obtain a treated base film; (4) contacting the treated base film with an organic solution containing a polyacyl chloride monomer and an acyl chloride monomer having a naphthalene ring structure to cause an interfacial polymerization reaction; (5) subjecting the reaction product of step (4) to air heating treatment to promote further cross-linking of the polyamide layer and volatilize the organic phase solution to obtain an initial nanofiltration membrane; (6) immersing the initial nanofiltration membrane in a citric acid solution for post-treatment to wash away unreacted monomers and additives; (7) washing the initial nanofiltration membrane after cleaning in step (6) with pure water at room temperature to cool the membrane, and then immersing it in a glycerol solution for pore preservation pretreatment; (8) taking out the nanofiltration membrane after the pore preservation pretreatment and heating and drying it to obtain the final product, a high-pressure resistant and high-salt concentration composite nanofiltration membrane.
2. The method for preparing the high pressure resistant high salt concentration composite nanofiltration membrane according to claim 1, characterized in that: In the casting solution of step (1), the mass fraction of polysulfone is 15-25 wt%; the content of the core-shell structure ternary copolymer is 10-30% of the mass of polysulfone; the core-shell structure ternary copolymer includes one or more of methyl methacrylate-butadiene-styrene copolymer, ethylene-butyl acrylate-glycidyl methacrylate copolymer, ethylene-methyl acrylate-glycidyl methacrylate copolymer, and ethylene-methyl methacrylate-glycidyl methacrylate copolymer; the hydrophilic additive is polyethylene glycol, the molecular weight of the polyethylene glycol is 200-100000 Da, and the content of polyethylene glycol is 3-5wt% of the mass of the casting solution; the stirring temperature of the casting solution is 75-85°C, the stirring time is 6 hours, vacuum degassing is used, and the casting solution is allowed to stand in an environment of 20-30°C.
3. The method for preparing the high pressure resistant high salt concentration composite nanofiltration membrane according to claim 2, characterized in that: In the casting solution described in step (1), the content of polysulfone is 21 wt%; the content of the core-shell structure terpolymer is 20% of the mass of polysulfone; the molecular weight of the polyethylene glycol is 2000 Da, and the content of polyethylene glycol is 4 wt% of the mass of the casting solution.
4. The method for preparing the high pressure resistant high salt concentration composite nanofiltration membrane according to claim 1, characterized in that: In step (2), the base film is composed of two parts, including a polysulfone layer and a non-woven fabric layer, the non-woven fabric layer is selected from one of polyester and polypropylene, and the base film has a thickness of 150-165 um.
5. The method for preparing the high pressure resistant high salt concentration composite nanofiltration membrane according to claim 1, characterized in that: In step (3), the aqueous solution of the polyamine monomer comprises: a polyamine monomer, a co-solvent, an acylation catalyst, an acid binding agent and water; The polyamine monomer is selected from one or more of m-phenylenediamine, p-phenylenediamine, o-phenylenediamine, mesitylenetriamine, ethylenediamine, 1,3,4-triaminobenzene, 3,5-diaminobenzoic acid, 2,4-diaminotoluene, diethylenetriamine, triethylenetetramine, piperazine, 1-ethylpiperazine, and polyethyleneimine. The polyamine monomer content in the aqueous solution containing the polyamine monomer is 0.1-10 wt %; The co-solvent is mainly selected from one or more of N-methylpyrrolidone, N-ethylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, ethanol, ethylene glycol, isopropanol, and dimethyl sulfoxide. The co-solvent content in the aqueous solution containing the polyamine monomer is 0.1-20wt%; The acylation catalyst includes 4-dimethylaminopyridine, and the acylation catalyst content in the aqueous solution containing the polyamine monomer is 0.01-1wt%; The acid binding agent is selected from one or more of a triethylamine / camphorsulfonic acid composite system, sodium hydroxide, potassium hydroxide, dipotassium hydrogen phosphate, and sodium carbonate. The amount of the acid binding agent is regulated by the pH value of the aqueous solution of the polyamine monomer, and the pH value of the aqueous solution is 10-11; The base film is in contact with the aqueous solution containing the polyamine monomer for 10 to 60 seconds.
6. The method for preparing the high pressure resistant high salt concentration composite nanofiltration membrane according to claim 5, characterized in that: In the aqueous solution containing polyamine monomers, the content of polyamine monomers is 1-5 wt %; and the content of co-solvents is 5-14 wt %.
7. The method for preparing the high pressure resistant high salt concentration composite nanofiltration membrane according to claim 1, characterized in that: In step (4), the polyacyl chloride monomer is an acyl chloride monomer having two or more acyl chloride groups; The content of the polyacyl chloride monomer is the total mass of the organic phase solution. of 0.05~1 wt%; The acyl chloride monomer having a naphthalene ring structure as the second monomer is mainly characterized by having a main naphthalene ring, and having 1 to 3 acyl chloride or sulfonyl chloride groups in its structure, The content of the acyl chloride monomer having a naphthalene ring structure is 0.01-1 wt % of the total mass of the organic phase solution. In the organic solution containing the polyacyl chloride monomer and the acyl chloride monomer having a naphthalene ring structure, the organic solvent is selected from one or more of the low polarity solvents n-hexane, n-heptane, cyclohexane, n-octane, Isopar M, Isopar H, Isopar L, Isopar E or Isopar G; The base film is in contact with the organic solution containing the polyacyl chloride monomer and the acyl chloride monomer having a naphthalene ring structure for 10 to 60 seconds.
8. The method for preparing the high pressure resistant high salt concentration composite nanofiltration membrane according to claim 7, characterized in that: In step (4), the acyl chloride monomer having two or more acyl chloride groups includes one or more of trimesoyl chloride, cyanuric chloride, isophthaloyl chloride, terephthaloyl chloride, phthaloyl chloride, biphenyl tetrachloride, biphenyl dichloride, benzene disulfonyl chloride, succinoyl chloride, glutaryl chloride, cyclobutane dichloride, and cyclohexane dichloride; the content of the polyacyl chloride monomer is the total mass of the organic phase solution. of 0.1~0.5 wt%.
9. The method for preparing the high-pressure resistant high-salt concentration composite nanofiltration membrane according to claim 7, characterized in that: The acyl chloride monomer having a naphthalene ring structure includes one or more of 1,3,6-naphthalenetrisulfonyl chloride, 2,6-naphthalene disulfonyl chloride, 2,7-naphthalene disulfonyl chloride, naphthalene-1,5-disulfonyl chloride, 2,6-naphthalenedicarboxylic acid chloride, 5-(dimethoxy)naphthalene-1-sulfonyl chloride, 1-naphthalenecarbonyl chloride, 2-naphthalenecarbonyl chloride, and 2-naphthalenesulfonyl chloride; the content of the acyl chloride monomer having a naphthalene ring structure is 0.02-0.5 wt%.
10. The method for preparing the high pressure resistant high salt concentration composite nanofiltration membrane according to claim 1, characterized in that: In step (5), the air heating temperature is 60-80° C., and the heating time is 1-5 minutes.
11. The method for preparing the high pressure resistant high salt concentration composite nanofiltration membrane according to claim 1, characterized in that: In step (6), the concentration of the citric acid solution is 0.5-10 wt %, the cleaning temperature is 60-80° C., and the cleaning time is 1-10 minutes.
12. The method for preparing the high pressure resistant high salt concentration composite nanofiltration membrane according to claim 1, characterized in that: In step (7), the normal temperature water is mainly 20-30°C pure water, and the cleaning time is 3-15 minutes; The concentration of the glycerol solution is 10-15 wt %, the temperature of the glycerol solution is 20-30° C., and the immersion time of the glycerol solution is 0.5-5 minutes.
13. The method for preparing the high pressure resistant high salt concentration composite nanofiltration membrane according to claim 12, characterized in that: In step (7), the cleaning time is 5 to 10 minutes; and the immersion time in the glycerol solution is 2 to 3 minutes.
14. The method for preparing a high pressure resistant high salt concentration composite nanofiltration membrane according to claim 1, characterized in that: In step (8), the heating and drying method adopts air heating and drying, the heating temperature is 60-90° C., and the heating time is 1-15 minutes.
15. The method for preparing the high pressure resistant high salt concentration composite nanofiltration membrane according to claim 14, characterized in that: In step (8), the heating temperature is 70-80°C.
16. A high pressure resistant high salt concentration composite nanofiltration membrane, characterized in that: The high-pressure and high-salt concentration composite nanofiltration membrane is prepared by the preparation method described in any one of claims 1 to 15.
Citation Information
Patent Citations
Aliphatic polyamide loose reverse osmosis membrane as well as preparation method and application thereof
CN108246128A
Production and manufacturing method of high-pressure nanofiltration membrane
CN114797495A
High-selectivity composite nanofiltration membrane and preparation method thereof
CN101934201A
Gas separation membrane, gas separation membrane element, and gas separation method
CN109906113A
Composite nanofiltration membrane and preparation method thereof
CN111686592A